The role of Akkermansia muciniphila in maintaining health: a bibliometric study - Gao, Fangfang; Cheng, Canyu; Li, Runwei; Chen, Zongcun; Tang, Ke; Du, Guankui (Frontiers in Medicine, 2025)
BackgroundAkkermansia muciniphila, as a probiotic, is negatively linked to IBD, obesity, and T2DM. The aim of this study was to comprehensively assess the research status of Akkermansia muciniphila over the past decade and explore the relationships between this bacterium and various health-related aspects.MethodsTools VOSviewer, Bibliometrix, and CiteSpace were used to analyze various aspects including publication metrics, contributors, institutions, geography, journals, funding, and keywords.ResultsOver the past decade, research on Akkermansia muciniphila has demonstrated a consistent annual growth in the number of publications, with a notable peak in 2021. China led in the number of publications, totaling 151, whereas the United States exhibited a higher centrality value. Among the 820 institutions involved in the research, the University of California (from the United States) and the Chinese Academy of Sciences (from China) occupied central positions. Willem M. De Vos ranked at the top, with 12 publications and 1,108 citations. The journal GUT, which had 5,125 citations and an Impact Factor of 23.0 in 2024, was the most highly cited. The most cited articles deepened the understanding of the bacterium’s impact on human health, spanning from basic research to translational medicine. Thirty-nine high-frequency keywords were grouped into five clusters, illustrating Akkermansia muciniphila’s associations with metabolic diseases, chronic kidney disease, the gut-brain axis, intestinal inflammation, and Bacteroidetes-Firmicutes shifts.ConclusionGiven Akkermansia muciniphila’s anti-inflammatory and gut-barrier-strengthening properties, it holds promise as a therapeutic for obesity, metabolic disorders, and inflammatory conditions. Therefore, future research should explore its potential further by conducting clinical trials, elucidating its mechanisms of action, and investigating its efficacy and safety in diverse patient populations.